Performance analysis of different fall detecting algorithms with different combinations of sensors. - Jhalak, Rashed Mahmood; Tonni, Fariya Rahman; Ibrahim, Ishaq Ibne; Rabbi, MD. Fazle (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.